Pemberdayaan Masyarakat Melalui Program Gerakan Makan Sayur Untuk Mencegah Komplikasi Ibu Hamil - Awatiful Azza; Danu Indra Wardhana (Journal of Community Development, 2022)
Vegetables are one of the sources of nutrition that are cheap and easy to obtain, especially in Jember Regency. Most of the people of Jember have jobs as capital in diversifying nutritional sources made from vegetables and are able to support the health status of the community. Complications of pregnant women is one of the health problems experienced by many pregnant women. Complications of pregnant women can be done by consuming healthy and diverse nutrition. However, hopefully people still don't know how to make processed food so that nutrition is maintained and more attractive. One effort that can be done is to empower mothers who are members of the posyandu to become the main pillar in helping prevent complications in pregnant women through the vegetable-eating movement program. Processed vegetable products are one of the creations to increase public support in consuming vegetables. The methods applied include the stages of preparation, implementation and evaluation. This stimulus community partnership program (PKMS) activity was carried out at the Posyandu Dusun Tgil, Kemiri Village, Panti District, Jember Regency, which was attended by 42 posyandu mothers consisting of 10 cadres, 2 midwives, and 30 posyandu members. Activities that have been carried out are in the form of counseling about the movement to eat vegetables, the benefits of vegetables for health and how to process vegetables so that the nutrients contained in them are not lost as well as healthy vegetable processing competitions by pregnant women. Based on the activities that have been carried out, there has been an increase in both the knowledge and skills of partners in processing vegetable-based foods as well as understanding the benefits of vegetables for pregnant women.